2022
DOI: 10.1158/1078-0432.ccr-22-0622
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Trial of Enhancing Immune Checkpoint Blockade by Stereotactic Radiation and In Situ Virus Gene Therapy in Metastatic Triple-Negative Breast Cancer

Abstract: Purpose: A Phase 2 trial of stereotactic radiation therapy and in situ cytotoxic virus therapy in metastatic triple-negative breast cancer (mTNBC) patients followed by pembrolizumab (STOMP) was designed to evaluate dual approach of enhancing single-agent immune checkpoint blockade with ADV/HSV-tk plus valacyclovir gene therapy and SBRT in mTNBC patients. Methods: In this single-arm, open-label Phase 2 trial, mTNBC patients were treated with ADV/HSV-tk (5 x 1011 vp) intratumoral injection, followed by SBRT to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“… 90 Another phase 2 trial includes 28 patients with metastatic TNBC to explore the value of in situ virus gene therapy (ADV/HSV-tk) plus stereotactic body radiotherapy and pembrolizumab, and the result demonstrated that clinical benefit rate was 21.4%, and patients with clinical benefit had durable responses, with improved median duration on treatment (9.6 months) and OS (14.7 months). 91 Use of microRNA in anti-cancer therapy also showed promising results in inhibiting breast cancer cell proliferation and development. MRX34, to our knowledge, is one of the first miRNA replacement agents (miR-34a), and now in entering clinical trials.…”
Section: Gene Therapymentioning
confidence: 99%
“… 90 Another phase 2 trial includes 28 patients with metastatic TNBC to explore the value of in situ virus gene therapy (ADV/HSV-tk) plus stereotactic body radiotherapy and pembrolizumab, and the result demonstrated that clinical benefit rate was 21.4%, and patients with clinical benefit had durable responses, with improved median duration on treatment (9.6 months) and OS (14.7 months). 91 Use of microRNA in anti-cancer therapy also showed promising results in inhibiting breast cancer cell proliferation and development. MRX34, to our knowledge, is one of the first miRNA replacement agents (miR-34a), and now in entering clinical trials.…”
Section: Gene Therapymentioning
confidence: 99%
“…Valacyclovir (VACV) could be rapidly converted to acyclovir by valacyclovirase (VACVase), a serine hydrolase in the liver (Figure B) . The cascade phosphorylation of acyclovir to a toxic form could then be performed by adenovirus-mediated expression of HSV-TK and CKs (Figure B). , Rabacfosadine (GS-9219, 112 ) is a prodrug of the acyclic nucleotide analogue 9-(2-phosphonylmethoxyethyl)­guanine (PMEG, 114 ) that was approved for the treatment of canine lymphoma. Rabacfosadine is first converted by cathepsin A to N6-cyclopropyl-9-(2-phosphonylmethoxyethyl)­diaminopurine (cpr-PMEDAP, 113 ) and then by aminohydrolase to PMEG.…”
Section: Biocatalytic Activation Of Prodrugsmentioning
confidence: 99%
“…73 Since immunotherapy alters the balance between immunity and immune tolerance, the increased likelihood of tumor recognition is accompanied by a higher immune response rate in normal tissues. In a Phase 2 trial of radioimmunotherapy for metastatic TNBC, 95 28 patients were enrolled and treated. Clinical benefit rate was seen in six patients (21.4%), and the median overall survival increased by more than 2-fold in patients with clinical benefit.…”
Section: Side Effects Of Radioimmunotherapymentioning
confidence: 99%